SURVEI MINAT MASYARAKAT TERHADAP PERMAINAN TONNIS DI KABUPATEN DEMAK (Department of Physical Education, Sport, Health and Recreation, 2014)
Tonnis game is pract icall y a new sport in t he community Demak, the game has a val ue t onnis practical, economical or cheap and give pleasure, so i t can be received wel l by the public. Issues raised in t his st udy is howthe public interest in t he game t onni s in Demak. The purpose of this study i s to det ermine how much publ icinterest in the game t onnis in Demak. Vari abl e in thi s study is the publ ic interest in t he game tonnis in Demak.To test the validty of using t he product moment formula and alpha rel iability test using the f ormul a. Dat a analysi s in this research is descript ive data analysis. The result s showed that the publ ic int erest in the gametonnis in Demak incl uded in t he category is as high as 132 respondents (48.88%) , 93 respondents (34.44%)incl uded in the high crit eria, 34 respondent s (12.59%) were incl uded in the criteria, and 11 respondents(4,074%) included in the low category. Concl usions based on t he results of t he study is that the average publ interest in playing on tonnis in Demak included in the very high cat egory. Advi ce from the author of, among others, for Unnes institutions shoul d be heavily socialized tonnis game, especially in the village knew nothing about the game tonnis that publ ic int erest in the game tonnis Demak increase even more so tonnis can grow more rapidly again.